2023
DOI: 10.1001/jamadermatol.2023.2077
|View full text |Cite
|
Sign up to set email alerts
|

Treatment With Ataluren for Wound Healing and Health Complications in a Patient With Junctional Epidermolysis Bullosa

Abstract: This case report describes an 11-year-old boy with widespread chronic wounds, frequent corneal erosions, dental caries, a tracheostomy, and failure to thrive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Orlowski et al reported a case of an 11-year-old boy suffering from junctional EB. 65 Treatment with orally administered PTC-124 three times daily at concentrations of 10-10-20 mg/kg (morning-noon-evening) were well tolerated. The drug was shown to significantly reduce the number and duration of hospitalization events during the treatment period and, thus, ameliorated the patient's skin condition as supported by the detection of low levels of laminin-332 subunits by immunofluorescence microscopy.…”
Section: Non -Aminog Lycos Ide Comp Oundsmentioning
confidence: 98%
See 1 more Smart Citation
“…Orlowski et al reported a case of an 11-year-old boy suffering from junctional EB. 65 Treatment with orally administered PTC-124 three times daily at concentrations of 10-10-20 mg/kg (morning-noon-evening) were well tolerated. The drug was shown to significantly reduce the number and duration of hospitalization events during the treatment period and, thus, ameliorated the patient's skin condition as supported by the detection of low levels of laminin-332 subunits by immunofluorescence microscopy.…”
Section: Non -Aminog Lycos Ide Comp Oundsmentioning
confidence: 98%
“…Orlowski et al. reported a case of an 11‐year‐old boy suffering from junctional EB 65 . Treatment with orally administered PTC‐124 three times daily at concentrations of 10–10–20 mg/kg (morning–noon–evening) were well tolerated.…”
Section: Non‐aminoglycoside Compoundsmentioning
confidence: 99%